The Labour Party since 1945 Old Labour - New Labour - Shaw, Eric 1949- (Making contemporary Britain series, 1999)
Eric Shaw focuses on the key areas of debate which illustrate Labour's unfolding aims and its responses to a range of pressures and constraints, namely economic policy, industrial policy, industrial relations and employment policy, and the nature of the welfare state. It is through discussion of these issues that he investigates the tension between traditionalism and modernization in the party and identifies the most significant influences behind change: Labour's organizational structure, rules and policy-making procedures; its distribution of power; its ethos and conventions; its electoral performance and the evolving social, economic and political environment of post-war Britain. Setting the dynamics of the Party within the context of dominant theories of party political change, the book also provides a significant contribution to debates on the nature of post-war British politics, useful for all students of contemporary history and political science